2012
DOI: 10.5578/tt.4018
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation and metabolic syndrome in stable COPD patients

Abstract: Stabil KOAH'lı hastalarda sistemik inflamasyon ve metabolik sendrom Giriş: Kronik obstrüktif akciğer hastalığı (KOAH) sistemik inflamasyonla ilişkili gibi görünen ekstrapulmoner etkilere sahiptir. Genel popülasyonda sistemik inflamasyonun önemli belirleyicilerinden biri olan metabolik sendromla KOAH arasındaki ilişki henüz netleşmemiştir. Bu çalışmanın amacı; farklı evrelerdeki stabil KOAH'lı hastalarda ve yaş, cinsiyet açısından eşleştirilmiş kontrol grubunda metabolik sendrom frekansını ve sistemik inflamasy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
4
17

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 38 publications
5
40
4
17
Order By: Relevance
“…The authors found that the frequency of metabolic syndrome was higher in the patient group than in the controls. Components of metabolic syndrome like abdominal obesity, hyperglycemia, and hypertension were significantly more prevalent in the patient group (8). In another study, metabolic syndrome and abdominal obesity were often found in patients with COPD (41).…”
Section: Total Oxidant Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found that the frequency of metabolic syndrome was higher in the patient group than in the controls. Components of metabolic syndrome like abdominal obesity, hyperglycemia, and hypertension were significantly more prevalent in the patient group (8). In another study, metabolic syndrome and abdominal obesity were often found in patients with COPD (41).…”
Section: Total Oxidant Statusmentioning
confidence: 99%
“…Akpınar et al studied 91 stable patients with COPD and 42 control subjects (8). The authors found that the frequency of metabolic syndrome was higher in the patient group than in the controls.…”
Section: Total Oxidant Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…KOAH'taki kardiyovasküler hastalık riskindeki artışının, hastalığın kendisiyle ilişkili sistemik enflamasyonun mu, yoksa ortak etiyolojik faktörlerin (yaş, sigara, cinsiyet, düşük sosyoekonomik düzey, vb.) bir sonucu mu olduğu halen aydınlatılmamış bir konudur (1,4).…”
unclassified
“…Ancak bu konuda yeterli veri yoktur. Metabolik sendrom prevalansının KOAH'lı olgularda daha yüksek olduğu bildirilmiştir (4,5). Çalışmamızda değerlendirdiğimiz risk faktörleri, metabolik sendrom komponentleri arasında da yer almaktadır (4).…”
unclassified